2021
DOI: 10.3389/fpsyg.2021.649574
|View full text |Cite
|
Sign up to set email alerts
|

How Do Upper Echelons Perceive Porter’s Five Forces? Evidence From Strategic Entrepreneurship in China

Abstract: Porter’s five forces model is an authoritative management tool used in analyzing the profitability and attractiveness of industries through an outside-in viewpoint. In the past decade, dramatic and rapid changes have prompted some criticism of the model. The comparison between new and old economy analysis makes the fundamentals of the model seem weak. Moreover, the past decade has shown that strategy and entrepreneurship in China are not completely dependent on the model. This study first aims to verify the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Contrary to the assertions of some scholars that Porter's framework has lost its relevance because of the rapid progress in globalization and digitalization, we suggest that the framework retains its relevance, especially in industries that are less susceptible to disruption (Brandenburger, 2002;Isabelle et al, 2020;Slater & Olson, 2002). Its relevance has been corroborated among entrepreneurs by Shi et al (2021) as well as by Grundy (2006: p. 227), who quoted an entrepreneur saying that he wished he knew about the framework when he was running his venture since it seemed highly relevant to his company's context.…”
Section: Discussion Implications and Concluding Remarkscontrasting
confidence: 90%
See 2 more Smart Citations
“…Contrary to the assertions of some scholars that Porter's framework has lost its relevance because of the rapid progress in globalization and digitalization, we suggest that the framework retains its relevance, especially in industries that are less susceptible to disruption (Brandenburger, 2002;Isabelle et al, 2020;Slater & Olson, 2002). Its relevance has been corroborated among entrepreneurs by Shi et al (2021) as well as by Grundy (2006: p. 227), who quoted an entrepreneur saying that he wished he knew about the framework when he was running his venture since it seemed highly relevant to his company's context.…”
Section: Discussion Implications and Concluding Remarkscontrasting
confidence: 90%
“…Its relevance has been corroborated among entrepreneurs by Shi et al. (2021) as well as by Grundy (2006: p. 227), who quoted an entrepreneur saying that he wished he knew about the framework when he was running his venture since it seemed highly relevant to his company's context.…”
Section: Discussion Implications and Concluding Remarksmentioning
confidence: 85%
See 1 more Smart Citation
“…This is a model for assessing and evaluating the position and competitive intensity of an enterprise. Porter's framework measures the performance and relevance of a business from a macro environmental perspective and sets to act as an effective tool in evaluating and assessing the position of a business in a dynamic market (Shi et al, 2021). Consequently, the foundation of a business is anchored on the Five Forces model, namely: bargaining power of suppliers and buyers; threat of new entrants; alternative products and services and rivalry by existing competitors.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2021) conducted a study in which they verified the sustainability of the five forces model and its subsequent integration into the Chinese business economy [15]. The study showed that the five forces model was used to control the profitability and attractiveness of the industry during startups and expansions.…”
mentioning
confidence: 99%